2009
DOI: 10.1055/s-0029-1216364
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Family-oriented Rehabilitation Program on the Quality of Life of Parents of Chronically Ill Children

Abstract: Taking part in family-oriented rehabilitation can improve the QoL of parents of children suffering from cancer, cardiac diseases or cystic fibrosis. Such programs could be expected to affect the way chronically ill children cope with their condition and this should be examined in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 10 publications
1
32
0
3
Order By: Relevance
“…Taken both, diagnostic and non‐diagnostic groups together, the mean QoL score of mothers was 51.05, indicating impaired QoL compared with other clinical parent populations . Fathers in our study sample reported significantly higher QoL (61.83) compared with mothers (p = 0.01).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Taken both, diagnostic and non‐diagnostic groups together, the mean QoL score of mothers was 51.05, indicating impaired QoL compared with other clinical parent populations . Fathers in our study sample reported significantly higher QoL (61.83) compared with mothers (p = 0.01).…”
Section: Resultsmentioning
confidence: 60%
“…Cronbach's alpha for the subscales was found to be between 0.75 and 0.88, for the global scale 0.91. Retest reliability is between 0.69 and 0.86 (30)(31)(32)(33). Moderate correlations with several scales of the SF-36 questionnaire, a well-known generic QoL questionnaire, were demonstrated (30).…”
Section: Main Outcome Parametermentioning
confidence: 99%
“…For parents of children with other chronic conditions (e.g. cystic fibrosis or cardiac disease) these programs are known to improve PQoL [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Both groups showed improved knowledge about cancer, less emotional symptoms, and higher family satisfaction as well as QoL at discharge from the FOR‐program compared with the baseline assessment. This might be explained by the fact that the control group already received an active family‐oriented intervention . Furthermore, only a small group of siblings showed higher symptoms of emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, specialized clinics set up a family‐oriented rehabilitation (FOR) program that offers medical and multimodal psychosocial interventions to patients and their families, including healthy children. This innovative approach takes into account the importance of all family members for therapeutic success and has been positively evaluated in several studies . In contrast to usual rehabilitation programs that focus solely on the chronically ill children, the FOR‐program includes parents and healthy children, who are classified as secondary patients in the rehabilitation program, based on the assumption that family functioning is a precondition for achieving the child's with cancer rehabilitation .…”
Section: Introductionmentioning
confidence: 99%